Alternative respiratory chain enzymes: Therapeutic potential and possible pitfalls - Saari, Sina; Garcia, Geovana S. [UNESP]; Bremer, Katharina; Chioda, Marina M. [UNESP]; Andjelkovic, Ana; Debes, Paul V.; Nikinmaa, Mikko; Szibor, Marten; Dufour, Eric; Rustin, Pierre; Oliveira, Marcos T. [UNESP]; Jacobs, Howard T. (Elsevier B.V., 2019)
The alternative respiratory chain (aRC), comprising the alternative NADH dehydrogenases (NDX) and quinone oxidases (AOX), is found in microbes, fungi and plants, where it buffers stresses arising from restrictions on electron flow in the oxidative phosphorylation system. The aRC enzymes are also found in species belonging to most metazoan phyla, including some chordates and arthropods species, although not in vertebrates or in Drosophila. We postulated that the aRC enzymes might be deployed to alleviate pathological stresses arising from mitochondria! dysfunction in a wide variety of disease states. However, before such therapies can be contemplated, it is essential to understand the effects of aRC enzymes on cell metabolism and organismal physiology. Here we report and discuss new findings that shed light on the functions of the aRC enzymes in animals, and the unexpected benefits and detriments that they confer on model organisms. In Clone intestinalis, the aRC is induced by hypoxia and by sulfide, but is unresponsive to other environmental stressors. When expressed in Drosophila, AOX results in impaired survival under restricted nutrition, in addition to the previously reported male reproductive anomalies. In contrast, it confers cold resistance to developing and adult flies, and counteracts cell signaling defects that underlie developmental dysmorphologies. The aRC enzymes may also influence life span and stress resistance more generally, by eliciting or interfering with hormetic mechanisms. In sum, their judicious use may lead to major benefits in medicine, but this will require a thorough characterization of their properties and physiological effects.
Keywords: Mitochondria; Mitochondrial disease; Thermogenesis; AOX; Reactive oxygen species